Lignin and lignin derivatives as components in biobased hot melt adhesives. Issue 38 (21st May 2019) - Laine, Christiane; Willberg‐Keyriläinen, Pia; Ropponen, Jarmo; Liitiä, Tiina
ABSTRACT: Hot melt adhesives (HMAs) are formulated for the first time with different lignins as major components, and the developed HMA formulations were tested for gluing paperboard. The best formulations showed equal or even better bond strength compared to a commercial HMA reference. A maximum bond strength of 16.1 N was achieved with a formulation of oxidized cellulose acetate, organosolv lignin, and triethyl citrate, whereas the bond strength of the commercial HMA reference was 10.5 N. The performance was adjusted via the selection of lignin, the formulation, and chemical modification. Lignin modification was not necessary but provided further possibilities for adjusting the properties for different products (reversible vs irreversible adhesive seams) and also for producing plasticizer‐free formulations. Modification with tall oil fatty acids enabled the formulation of fully biobased HMAs without any external plasticizer and provided a bond strength as high as high as 8.9 N. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47983. Abstract :